Sharia Fintech and Gen Z: The Mediating Role of Perceived Usefulness - Hakim, M. Arif; Supriyanto, Agus (Faculty of Islamic Economics and Business, Universitas Islam Negeri Ar-Raniry, 2024)
This study investigates the mediating role of perceived usefulness in the adoption of Sharia fintech among Generation Z individuals in Java Island, Indonesia. A sample of 155 respondents, selected through purposive sampling, participated in the research. Data analysis was conducted using Structural Equation Modeling (SEM) with AMOS 25.0. The findings reveal that perceived usefulness successfully mediates the influence of subjective norms on behavioral intention. Furthermore, perceived usefulness fully mediates the impact of perceived ease of use on behavioral intention. These results underscore the importance of fintech managers gaining deeper insights and aligning service development with market needs. Sharia fintech companies should emphasize the benefits of technology use to enhance user interest in fintech adoption. Given Indonesia's predominantly Muslim population, ensuring user-friendly technology is crucial. This study contributes to the understanding of the factors driving the adoption of Sharia fintech and offers practical implications for fintech service providers.========================================================================================================ABSTRAK – Fintech Syariah dan Generasi Z: Peran Mediasi Perceived Usefulness. Penelitian ini mengkaji peran mediasi perceived usefulness dalam adopsi fintech syariah di kalangan Generasi Z di Pulau Jawa, Indonesia. Data dikumpulkan melalui kuesioner dari 155 responden yang dipilih dengan metode purposive sampling. Hasil analisis data menggunakan Structural Equation Modeling (SEM) dengan AMOS 25.0, menunjukkan bahwa perceived usefulness dapat memediasi pengaruh norma subjektif terhadap niat perilaku. Lebih lanjut, perceived usefulness memediasi secara penuh dampak persepsi kemudahan penggunaan terhadap niat perilaku. Hasil ini menujukkan pentingnya wawasan mendalam bagi pengelola fintech untuk dapat menyelaraskan pengembangan layanan dengan kebutuhan pasar. Perusahaan fintech syariah harus menekankan manfaat penggunaan teknologi yang user friendly untuk meningkatkan minat pengguna dalam adopsi fintech. Hal ini berkaitan dengan ajaran Islam yang dipercayai oleh mayoritas penduduk Indonesia. Penelitian ini berkontribusi dalam memberikan pemahaman akan faktor-faktor yang mendorong adopsi fintech syariah dan menawarkan implikasi praktis bagi penyedia layanan fintech.